THE ROLE OF MASS MEDIA IN INFLUENCING ATTITUDES TOWARDS PARTICIPATION IN FAMILY PLANNING PROGRAM: AN ANALYSIS OF INDONESIAN DEMOGRAPHY AND HEALTH SURVEY DATA, 2007 - Rohdhiana Sumariati; Dewi H. Susilastuti; Agus Heruanto Hadna (Faculty of Pharmacy, Universitas Gadjah Mada)
As an effort to boost the issue of family planning program, BKKBN has adopted a policy of IEC (Information Communication and Education) as a promotional effort and community mobilization to increase demand for contraceptives.This study aim was to analyze the role of mass media in influencing attitudes towards participation of family planning. Research was performed by using the Indonesian Demography and Health Survey data (“SKDI” 2007). Sampling location was national-wide which included all 15-49 years old ever-married women and lived in Indonesia. Informan was determined by purposive sampling technique. Total sample was 32,895 women. Data was analyzed by chi-square test. The results showed that 57.4% of ever-married women had a positive attitude towards family planning program and participated in th family planning program with p=0.005 (p value = 0.000). While ever-married women who were exposed to family planning messages through mass media and become participants KB was 58.3%, with p=0.005 (p value = 0.000). The relationship of mass media’s role in influencing attitudes towards family planning participation was observed with the control variables of education level, residence, motivation to have more children and the number of children (alive), each of which showed a significant relationship with p=0.005 (p value = 0.000). Television is the medium which attract most viewers. Different model is required for the highly educated women. The emergence of other media such as religious leaders, community, doctors, midwives, and family planning cadres can be used as a vehicle for delivering messages and information. It needs a strategy of repetition (redundancing) messages and information, in order to remind people about the importance of the family planning programs. The right design in campaigning and informing the family planning program should be made after considering whether the type of media used is matched witu geographical characteristics, time, and forms of contraception.Keywords: mass media, attitudes, participation in Family Planning Program